A Value at Risk Approach to Measuring Equity Trading Risk Exposure in Emerging Stock Markets - Mazin A. M. Al Janabi (Asian Academy of Management Journal of Accounting and Finance, 2007)
The attempt of this article is to fill a gap in the equity trading risk management literature and particularly from the perspective of emerging and illiquid financial markets, such as in the context of the Moroccan stock market. This paper provides real-world risk management techniques and strategies that can be applied to equity trading/investment portfolios in emerging markets. In this work, we divulge a proactive approach for the measurement/management of risk exposure for financial trading portfolios that contain illiquid equity securities. This approach is based on the renowned concept of Value At Risk (VAR) along with the creation of a software tool utilizing matrix-algebra technique. The recommended feasible analytical/quantitative techniques and procedures can be utilized in almost all-emerging economies, if they are tailored to match-up with each market's initial level of complexity. In order to exemplify the appropriate use of VAR and stress-testing techniques, real-world examples and attainable reports of risk management are presented for the Casablanca Stock Exchange (CSE). To this end, some case studies are accomplished with the intent of creating a realistic framework of equity trading risk measurement and control reports.